2010
DOI: 10.1152/japplphysiol.00135.2010
|View full text |Cite
|
Sign up to set email alerts
|

Skin temperature modifies the impact of hypohydration on aerobic performance

Abstract: Kenefick RW, Cheuvront SN, Palombo LJ, Ely BR, Sawka MN. Skin temperature modifies the impact of hypohydration on aerobic performance. J Appl Physiol 109: 79 -86, 2010. First published April 8, 2010 doi:10.1152/japplphysiol.00135.2010.-This study determined the effects of hypohydration on aerobic performance in compensable [evaporative cooling requirement (E req) Ͻ maximal evaporative cooling (E max)] conditions of 10°C [7°C wet bulb globe temperature (WBGT)], 20°C (16°C WBGT), 30°C (22°C WBGT), and 40°C (27°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
126
4
7

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(149 citation statements)
references
References 39 publications
12
126
4
7
Order By: Relevance
“…It is well known that the effects of hypohydration on exercise performance are more profound in hot than temperate environments (Kenefick et al 2010). The present study implicates the hypohydration and reduced plasma volume observed during severe ER with fatigue during exercise, at least in the heat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the effects of hypohydration on exercise performance are more profound in hot than temperate environments (Kenefick et al 2010). The present study implicates the hypohydration and reduced plasma volume observed during severe ER with fatigue during exercise, at least in the heat.…”
Section: Discussionmentioning
confidence: 99%
“…This hypohydration appears to be caused by the continued excretion of electrolytes in urine, despite little or no intake (James and Shirreffs 2013), and might be offset by electrolyte supplementation during severe ER (Consolazio et al 1968a). Hypohydration reduces endurance capacity and performance (Cheuvront and Kenefick 2014), an effect that is exacerbated as environmental temperature increases (Kenefick et al 2010). Therefore, the hypohydration, and particularly plasma volume reduction, that accompanies severe ER might negatively impact on exercise capacity (Cheuvront and Kenefick 2014), particularly if exercise is undertaken in a hot environment.…”
Section: Introductionmentioning
confidence: 99%
“…They found that with skin-surface cooling, the operating point of the PCWP-SV curve was shifted to the right onto the flatter part of the hyperbolic curve. Even when dehydrated up to 4% body mass, cold exposure (8 • C air) maintains stroke volume during 30-min of exercise at 72% VO 2max (108), leading to no change in cardiac output (Q); this is likely related to the relatively small changes in exercise performance when dehydrated in cool to cold, versus warm, environments (43,142). Cardiac output during exercise in the cold is dependent on exercise intensity.…”
Section: Cardiovascular Limitationsmentioning
confidence: 99%
“…Above a certain threshold, thermoregulatory responses are evoked (Johnson and Park, 1982), including cutaneous vasodilation which promotes an increase in skin blood flow for dry heat loss from the skin to the environment. The extent to which T s and T re converge (ranging from 0.1 °C to 1.5 °C in the current study) depends upon the temperature of the microclimate (Kenefick et al, 2010), but once thermal equilibrium between the two measures is reached, T re and T s should rise in parallel. In GTS and PRPS, T is and T re converged for the first 20 to 30 min of exercise, after which they increased in parallel for the remainder of the trial.…”
Section: Discussionmentioning
confidence: 65%
“…This was also shown by McLellan et al (1993) where the difference between T re and mean T s was 1.3 °C and 2.2 °C when ambient temperatures were 30 °C and 18 °C, respectively, for firefighters carrying out heavy work in CBRN PPE. Microclimate temperature clearly has a direct impact on the degree to which T is and T re converge (McLellan et al, 1993, Kenefick et al, 2010, and the inclusion of T mc in the equation (equation 3) improves the prediction of T re . However, T mc is subtracted, or inversely in the equation, which is counterintuitive based on the assumption that as T mc increases, capacity for heat loss decreases, which is likely to result in an increase in T re .…”
Section: Discussionmentioning
confidence: 99%